An Iron Oxide Nanocarrier Loaded with a Pt(IV) Prodrug and Immunostimulatory dsRNA for Combining Complementary Cancer Killing Effects. Issue 7 (2nd April 2015) - Hernández‐Gil, Javier; Cobaleda‐Siles, Macarena; Zabaleta, Aintzane; Salassa, Luca; Calvo, Javier; Mareque‐Rivas, Juan C.
<x xml:space="preserve">Abstract</x> There is major current interest in harnessing the immune system against cancer and in developing drugs that provide complementary cancer killing mechanisms. Although the recent advent of nanoparticle‐based drug delivery systems has improved the efficacy of platinum drugs for chemotherapy, one of the fundamental paradigms in their design and use is evading surveillance by the immune system to enhance anticancer efficacy. However, new studies are showing that chemotherapy can profit from actively targeting stimulation of the immune system and that suitably functionalized nanomaterials might be ideal for overcoming some key challenges in immunotherapy. Pt(IV) prodrug–modified PEGylated phospholipid micelles that encapsulate biocompatible iron oxide nanoparticles (IONPs) as a new delivery system for cisplatin are reported. The Pt(IV)–IONPs are functionalized with polyinosinic–polycytidylic acid (poly (I:C))—a double stranded RNA (dsRNA) analog widely used as an adjuvant in clinical trials of cancer immunotherapy. The Pt(IV)–IONPs and poly (I:C)–Pt(IV)–IONPs enhance by more than an order of magnitude the prodrug cytotoxicity in different tumor cells, while greatly increasing the ability of cisplatin and poly (I:C) to activate dendritic cells—the key cellular players in immunotherapy. The results suggest that these constructs hold promise for targeted chemoimmunotherapy.